Catholic Integral Ecology Perspective on Lithium Mining—Building Common Ground and Action with Indigenous Communities (2025)
This paper argues for the need to rethink lithium mining and, more broadly, for the so-called sustainable development policies grounded upon it, especially in Chile. Based on perspectives from integral ecology and Pope Francis’ critique of the technocratic paradigm, this paper questions the ways in which lithium mining is currently done, taking into account its disregard for the environment and Indigenous people’s ancestral rights. After explaining the current and future tendencies of lithium mining and their environmental impact, the paper deepens our understanding of integral ecology, particularly through its critique of the technocratic paradigm, which Pope Francis identifies as the root cause of the current socio-environmental crisis. It also argues that the leadership of the Catholic church takes a proactive stance by understanding and enriching integral ecology with Indigenous wisdom. Such efforts could build a common project to protect the environment with dwellers of the land where lithium mining takes place. Though cooperation is needed to drive lithium mining firms to pursue environmentally friendly practices, collaboration between these groups remains scarce at the grassroots level.